The Relationship Between Teacher Readiness And Thematic Learning Outcomes In Cluster 2 Tamalate District, Makassar City - Nurul Fatwa; Nur Abidah Idrus (International Journal of Elementary School Teacher, 2023)
This research is a quantitative research with a correlational type which aims to look at the relationship between teacher readiness and thematic learning outcomes for Class V elementary schools in Cluster 2, Tamalate District, Makassar City. This research instrument uses a questionnaire and documentation. Based on the descriptive statistics table, teacher readiness has low (50%), medium (17%), and high (33%) categories. Class V student learning outcomes), 37% in the score category 61-80 (high) and 26% in the score category 41-60 (moderate). This study used the Kolmogrov-Smirnov test with a sig value of 0.200 > 0.05 so it can be concluded that the variable data on teacher readiness and learning achievement are normally distributed. In terms of testing with a significance level of 5% based on the calculation results it is known that the significance value is 0.877 > 0.05 so that there is a linear relationship between the variables. Based on the results of the product moment correlation analysis, the relationship between teacher readiness and learning outcomes of fifth grade elementary school students in Cluster 2 Tamalate District, Makassar City, obtained a value of -0.204 while it was 2.77645 at a significant level of 5 % and N = 6. From the results of this analysis it can be seen that the value < (-0.204 < 2.77645 ). Based on this analysis, it can be concluded that there is no significant relationship between teacher readiness and learning outcomes of fifth grade elementary school students in Cluster 2, Tamalate District, Makassar City.Keywords: teacher readiness, learning outcomes, relationships